Long-term impact of different prevalent cropping systems on soil physico-chemical characteristics under subtropical climate conditions of Punjab, Pakistan - Fahad Ali Fayyaz; Irfan Aziz; Muhammad Ansar; Muhammad Akmal; Saud Alamri; Alanoud T. Alfagham; Renata Gamrat; Abdul Qayyum (Scientific Reports)
Abstract Lack of site-specific nutrients information for different cropping systems has been a major challenge in addressing declining soil fertility levels and enhance crop productivity in Punjab, Pakistan. Therefore, the study was designed to assess and quantify soil physico-chemical characteristics, crop yield and economic feasibility of different cropping systems (CS), including groundnut-wheat (G-W), rice-wheat (R-W), fallow-gram/wheat (F-G/W), mix cropping (Mix C) and cotton-wheat (C-W). A total of 470 georeferenced soil samples were collected using a random survey approach, and the samples were analyzed for soil texture, pH, electrical conductivity (EC), organic matter percentage (OM), total nitrogen percentage (TN), accessible phosphorus (AvP) (mg kg−1) and extractable potassium (ExK) (mg kg−1). For crop yield and economic feasibility, the data collected for each crop were summed up and mean data for every cropping system were compared. Cotton-wheat cropping system had the highest mean value of EC (1.57 dS/m), while mix cropping showed the maximum level of OM (0.53%), TN (0.028%), AvP (5.16 mg kg−1), yield (10.09 t ha−1), gross revenue (PK Rs. 87,883) and benefit cost ratio (2.2). The R-W cropping system had the highest pH (8.37), ExK (127.39 mg kg−1) and total cost (PK Rs. 46,882.25). Curiously, the fallow-gram/wheat cropping system had lower value of OM, TN, AvP, ExK, yield, GR and BCR, highlighted its poor performance compared to mix cropping system. Deficiencies in OM were widespread across all cropping systems, with only 3.1% of samples under mix cropping system being in the medium range. Similarly, TN %, AvP and ExK were deficient in varying degrees across all cropping systems, particularly in the fallow-gram/wheat cropping system. Spatial variability maps showed that nutrient deficiencies were more pronounced from the southern to northern side of study area. Our findings indicate that mixed cropping can improve soil health and enhance crop productivity, supporting the need for targeted nutrient management in Punjab agriculture systems.